An outlook on nutrition and food labelling among selected school children aged 10-12 years in Coimbatore city - M. C., Anitha; K., Anusuya Devi (International Journal Of Community Medicine And Public Health, 2017)
Background:Use of nutritional labels in choosing food is associated with healthier eating habits including lower fat intake. Current public health efforts have focused on the revamping of nutritional labels to make them easier to read and use for the consumer. The objective of this study is to assess the frequency of use of nutritional labels and find out the awareness of nutrition labels. Methods:The study was designed to find the awareness among 1409 school children constituting both boys and girls from various boards like Government, Government aided, Matriculation and CBSE schools aged 10-12 years in Sundrapuram, Coimbatore city. The structured and validated questionnaire on basic information like Personal Information, socio-economic information, anthropometry and frequency and awareness nutrition labelling was made by asking dichotomous questions. Results:Many children who belong to low-income do not regularly use the nutrition facts panel information. Conclusions:The study took initiative in creating knowledge through demonstration on facts about Nutrition Labeling.